Simulation design and execution: The case of TRAFIL - Christos Bouras; Kostas Stamos; G Kioumourtzis; Savvas Charalambides; Michalis Drakoulelis (3rd Intenational Conference on Simulation and Modeling Methodologies, Technologies and Applications, Reykjavvk, Iceland, 2013)
This paper presents the enhancements that we have done on the TRAFIL (TRAce FILe) framework, which significantly extend its capabilities in the areas of simulation design and execution. In particular, TRAFIL now offers the possibility to design, create, execute and review NS-2 simulation scenarios, on top of its ex-isting post-simulation trace analysis functionalities. The enhancements make TRAFIL a complete wrapper around the NS-2 simulator, allowing the user to perform all steps from pre-simulation design to actual simu-lation execution in an automated way and fast and convenient post-simulation analysis of potentially large amount of data. The paper describes the new TRAFIL architecture and how these enhancements were im-plemented with the goal of relieving NS-2 users from the often cumbersome tasks of script writing and vali-dating, while also enabling them at to go behind the TRAFIL environment and into the simulator internals at any time. The paper presents the new GUI functionalities developed for that purpose, the approach that we took for their design and how these fit in the overall TRAFIL architecture.